Efek Ekstrak Etanol Daun Cacao Theobroma Cacao L. terhadap Aktifitas Sistem Saraf Pusat - Zet Rizal; Harto H.; Helmi Arifin (Jurnal Farmasi Higea, 2009)
The research about stimulant activity of the central nervous system from the ethanol extract of cacao leaves ( Theobroma cacao L.) to mice ( Mus musculus ) has been done. The observation of stimulant activity from the other doses gives to experiment of animal with oral. It does with rota – road tools, the motoric of activity test, automatichole board tools and the times of inductive sleep and the long time sleep by mice with 50 mg/Kg BB i.p doses. The finalty reseach knows that ethanol extract of cacao leaves with 250 and 500 mg/Kg BB doses characteristic stimulant. It looks that mount the power of venture, activity motoric, feel knows, the time of inductive sleep and the short time with experiment of animal if it compare with control group.